Spanish ratification of the Luxembourg Protocol to the Cape Town convention : the entering into force of the international legal rules for railway rolling stock finance - Rodríguez de las Heras Ballell, Teresa (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The deposit of the instrument of ratification by Spain to the Luxembourg Protocol on international interests related to railway rolling stock, the second protocol to the Cape Town Convention, put into motion the entering into force of the Protocol once the International Registry will be fully operative. The Spanish ratification is of great importance for the expansion of the Cape Town system, for the position of Spain as a Contracting State, and for the access to credit in the railway sector. This Paper studies the ratification of Spain to the Luxembourg Protocol, enabling it to enter into force, analyzes the declarations made by Spain to the Protocol within the framework of the Cape Town system and considering the equipment-specific provisions.
Keywords: railway rolling stock; wagons; financing; security interests; Cape Town Convention; Luxembourg Protocol; leasing; International Registry